Revision of the Australian Sphaerodoridae (Annelida) including the description of four new species - Capa, Maria; Bakken, Torkild (Zootaxa, 2015)
A revision of the complete sphaerodorid (Sphaerodoridae, Annelida) collections housed in the three major Australian museums (The Australian Museum, Museum and Art Gallery of the Northern Territory and Museum Victoria) has been performed. Specimens of three of the four species described to date from Australian waters, Ephesiella australiensis, Sphaerodoropsis exmouthensis and Sphaerodoropsis fauchaldi, have been re-encountered, resulting in changes to their previously reported distribution range. Four additional species are herein described as new: Sphaerephesia hutchingsae n. sp., Sphaerodoropsis longofalcigera n. sp., Sphaerodoropsis megatuberculata n. sp. and Sphaerodoropsis wilsoni n. sp. Moreover, Sphaerodoropsis multipapillata heteropapillata is elevated to the rank of species. A formal description of other specimens, most likely belonging to undescribed species, is not possible due to insufficient material, but information about some of their morphological features is provided. Descriptions, iconography, geographical and ecological information of all species part of this revision is provided together with a key for identification to all Australian species. An evaluation of some of the traditional generic taxonomic features is made, considering the variation observed within the Australian species.